Influence Of Force Reduction Factor On The Interstorey Drift Of RC Building Under Repeated Near-Field Earthquake - Adiyanto, Mohd Irwan (2011)
Current practices in earthquake engineering only apply single earthquake motion on building structure during modelling and analysis. However, in real earthquake event, the tremors always occurred repeatedly until two or three times after the first tremor. This phenomenon can affect the stiffness and strength of the structural system. Due to lack of time any rehabilitation action is impractical. Thus, the building may experience greater damage due to several repeated tremors. This thesis presents the seismic performance of 3 and 18 storey generic reinforced concrete building subjected to single and repeated earthquake.